Efficiency of the subsidized regime entities in Colombia by means of data envelopment analysis - Fontalvo Herrera, Tomás José (Universidad y Salud, 2014)
In this research, an analysis of the technical efficiency of the entities that are part of the subsidized regime in Colombia during 2010 was made. The nonparametric Data Envelopment Analysis (DEA) approach was used, specifically the CCR-O model, which focuses on outputs to evaluate the efficiency of the sector. The Superintendence of Health was taken as a source of used information. From the 26 organizations studied, 15 presented low efficiency, 2 presented medium efficiency, 3 presented high efficiency, and 6 entities proved to be fully efficient. These entities were: Capresoca EPS, fund of welfare communications Caprecom, benefit society in Choco Comfachoco, benefit society in Nariño, benefit society in Cordoba Comfaco and benefit society in Huila Comfamiliar Huila. It could be concluded that 23.08% of DMU’s evaluated showed optimum efficiency. The average efficiency of the study population was 65.85%.